2016
DOI: 10.1016/j.pmatsci.2016.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Functional properties of ceramic-Ag nanocomposite coatings produced by magnetron sputtering

Abstract: In recent years, the use of nanocomposite materials to functionalize surfaces has been investigated, taking advantage of the complementary properties of the nanocomposite constituents. Among this family of materials, ceramic-Ag coatings have been widely studied due to the large variety of functionalities that silver possesses and the possibility of tuning the coating's practical features by selecting the proper matrix to support this noble metal. Therefore, this review focuses on the effects of silver nanopart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(49 citation statements)
references
References 145 publications
(480 reference statements)
3
46
0
Order By: Relevance
“…Recently, soft metals (such as silver, aluminum, and copper) were added into TMN based films to reduce the friction coefficient over a wide temperature range [7][8][9]. As expected, a novel self-lubricated CrN-Ag nanocomposite film was elucidated by Mulligan et al [10], indicating that the addition of…”
Section: Introductionmentioning
confidence: 77%
“…Recently, soft metals (such as silver, aluminum, and copper) were added into TMN based films to reduce the friction coefficient over a wide temperature range [7][8][9]. As expected, a novel self-lubricated CrN-Ag nanocomposite film was elucidated by Mulligan et al [10], indicating that the addition of…”
Section: Introductionmentioning
confidence: 77%
“…This study was unique as there are no prior studies reporting on antibacterial effects of hybrid composite metal-ceramic materials. However, studies on antibacterial effects of Ag-containing ceramic materials have been previously published [18]. In general, those studies have shown the relationship between the amount of silver in the ceramic surface and antibacterial activity [19] and the importance of segregation and agglomeration of silver on the surface for improving antibacterial efficacy [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these coatings allow adding other functional properties, such as enhanced osseointegration, which is highly desirable for dental implants, enhanced wear resistance of joint prosthesis, or improved hemocompatibility of cardiovascular devices. Several reports have evaluated the applicability of DLC [94], DLC containing different elements, namely, N [53,57], Pt:Ru [57], Ti [12,52], Cr [12], compounds such as TiN [71,92,100], AlN [92], TiAlN [92,101], ZrN [19,102], silicon-containing ZrN [38], CrN [103], ZrCN, and Ag-containing ZrCN [87,104], Hf-containing ZrCN [10] as coatings for different biomedical applications. The main conclusions in relation to each of these coatings are summarized in Table S1 (Suplementary information).…”
Section: Electrochemical Corrosion Behaviour Of Men Mecn and A-c-bamentioning
confidence: 99%
“…Figure 7 shows a statistical analysis of the electrolytes used in the reports related to MeN-, MeCN-, and a-C-based coatings proposed for different biomedical applications. As depicted in Figure 7 some of the papers used simple saline solutions containing NaCl, with varying concentrations of the salt (from 0.9% [11,87,100,104], which resembles the physiological concentration, up to 3% of NaCl [103]), while the other electrolytes were represented by more complex saline solutions (phosphate buffer solution (PBS) [81,105], Hank's balanced saline solution (HBSS) [52,57], or simulated body fluid (SBF) [12,92,106,107]), which can contain some organic molecules such as in Tyrode"s simulated body fluid and AFNOR S90-701 artificial saliva [19,102] and Fusayama Mayer artificial saliva [101]. The addition of proteins to SBF was also performed.…”
Section: Corrosion Behaviour Of Coatings In Simulated Body Fluids Andmentioning
confidence: 99%